2021
DOI: 10.3390/cryst12010050
|View full text |Cite
|
Sign up to set email alerts
|

Rietveld Refinement and X-ray Absorption Study on the Bonding States of Lanthanum-Based Perovskite-Type Oxides La1−xCexCoO3

Abstract: Metal-oxygen bonding of the Ce-doped LaCoO3 system remains largely unexplored despite extensive studies on its magnetic properties. Here, we investigate the structure and local structure of nanoscale La1-xCexCoO3, with x = 0, 0.2, and 0.4, using the Rietveld refinement and synchrotron X-ray absorption techniques, complemented by topological analysis of experimental electron density and electron energy distribution. The Rietveld refinement results show that LaCoO3 subject to Ce addition is best interpretable by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The fit goodness (S) is defined as the ratio between the weighted pattern (R wp ), and the expected values (R exp ) (S = R wp / R exp ). The refinement was maintained until a value of S close to one was found to be convergent, which validates the value of refinement [26][27][28]. The refinement parameters values as well as the lattice parameter and the crystallite size are shown in table 1, which suggests a rather good precision in synthesizing the spinel thin films without any additional phases.…”
Section: X-ray Analysissupporting
confidence: 67%
“…The fit goodness (S) is defined as the ratio between the weighted pattern (R wp ), and the expected values (R exp ) (S = R wp / R exp ). The refinement was maintained until a value of S close to one was found to be convergent, which validates the value of refinement [26][27][28]. The refinement parameters values as well as the lattice parameter and the crystallite size are shown in table 1, which suggests a rather good precision in synthesizing the spinel thin films without any additional phases.…”
Section: X-ray Analysissupporting
confidence: 67%
“…73-1963) [4648]. The cell parameters of Mg 0.4 Co 0.5 Zn 0.1 Fe 2 O 4 nanoparticles were a = b = c = 8.3919 true A ̊ , α = β = γ = 90 ° , and the volume of 590.99 Å 3 , which suggested that Mg 0.4 Co 0.5 Zn 0.1 Fe 2 O 4 nanoparticles were cubic type [49]. The hysteresis loops of Mg 0.4 Co 0.5 Zn 0.1 Fe 2 O 4 nanoparticles were shown in Figure 1(d), and the saturation magnetization (M s ) was 13.5 emu·g -1 , which contributed to being separated after adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Then, magnetic glassy carbon electrode, Ag/AgCl electrode, and platinum wire electrode were regarded as the working electrode, the reference electrode, and the counter electrode, respectively; 0.1 M KCl was used as the electrolyte which contained 5 mM [Fe(CN) 6 ] 3-/4-. the volume of 590.99 Å 3 , which suggested that Mg 0.4 Co 0.5 Zn 0.1-Fe 2 O 4 nanoparticles were cubic type [49]. The hysteresis loops of Mg 0.4 Co 0.5 Zn 0.1 Fe 2 O 4 nanoparticles were shown in Figure 1(d), and the saturation magnetization (M s ) was 13.5 emu•g -1 , which contributed to being separated after adsorption.…”
Section: Adsorptionmentioning
confidence: 96%